Autoantibodies Directed Against CD43 Molecules With an Altered Glycosylation Status on Human Immunodeficiency Virus Type 1 (HIV-1)-Infected CEM Cells Are Found in All HIV-1+ Individuals - Giordanengo, Valerie; Limouse, Martine; Roure, Laurence Desroys Du; Cottalorda, Jacqueline; Doglio, Alain; Passeron, Alain; Fuzibet, Jean-Gabriel; Lefebvre, Jean-Claude (Blood, 1995)
Autoantibodies to lymphocytes have been detected in sera from human immunodeficiency virus type 1 (HIV-1 (infected individuals, and several autoantigens have been described. Among them, hyposialylated CD43 has been shown to be a target for autoantibodies in up to 47% of HIV+ individuals. However, the corresponding autoantigen fie, the incompletely sialylated CD43) has not been isolated from blood cells of HIV-1-infected individuals. Recently, we have observed in vitro that HIV-1 productively or latently infected CEM cells (CEMLAI/NP) express CD43 molecules with modified glycosylation (mogly CD43). Using CEMLAI/NP cells, which do not express any structural viral antigen, we show now that all of the tested HIV+ sera from asymptomatic individuals, and up to 86% of those from subjects at the acquired immunodeficiency syndrome stage contain antibodies (mainly IgM and, to a lesser degree, IgG) that recognize the surface of CEMLAI/NP cells, and precipitate mogly CD43 molecules from the cells lysates. Taken together with our previous demonstration of altered glycosylation of CD43 from HIV-1-infected CEM cells in vitro, the constant anti-mogly CO43 autoimmune response observed from asymptomatic HIV-1+ subjects is likely to illustrate the occurence of an altered glycosylation in vivo of the major lymphocyte surface CD43 glycoprotein, associated with HIV-1 infection.